The discontent of social scoring through state surveillance using the Chinese social credit system as a case study - Van Zyl, Danielle (School of Economics, 2026)
Many governments worldwide, particularly in democratic countries, are rapidly implementing surveillance technologies and expanding their surveillance programs, causing widespread concern. Although these governments claim to use this technology exclusively for ensuring safety and security of citizens, it has also facilitated unchecked control and power abuse by the state. The COVID-19 pandemic made many such abuses glaringly evident. Governments and private companies have partnered to create advanced surveillance programs that generate unprecedented amounts of personal data. This literature review explores the increased use and advancement of state surveillance systems worldwide and the extent to which citizens are identified and tracked. Social credit scoring systems are understood using the Chinese Social Credit Scoring System (CSCSS) as a case study. This paper evaluates the potential use of social scoring systems to enhance the state's surveillance capabilities to influence, control, and extend its power over citizens. The paper explores the current limitations of the CSCSS and analyses the creation of similar future systems in the West. State-controlled scoring systems can completely change the state's role in society, including how it governs and enforces legislation. Analysing the CSCSS highlights the difficulty of creating fair and integrated social credit systems that use incentive mechanisms to alter behaviour. The potential harms of a social credit system to citizens are vast. Concerns about individual privacy and the abuse of power are valid; however, the unfair treatment of minorities and the oppression of political opponents are additional concerns under algorithmic rule. Current regulation is insufficient to protect citizens' privacy as surveillance scoring programs become more far-reaching and invasive over time.